2022
DOI: 10.1101/2022.06.16.22276402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dysfunctional cortical gradient topography in treatment resistant major depression

Abstract: Background Treatment-Resistant Depression (TRD) refers to patients with major depressive disorder who do not remit after two or more antidepressant trials. TRD is common and highly debilitating, but its neurobiological basis remains poorly understood. Recent neuroimaging studies have revealed cortical connectivity gradients that dissociate primary sensorimotor areas from higher-order associative cortices. This fundamental topography determines cortical information flow and is affected by psychiatric disorders… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This network is composed of the inferior frontal sulcus, regions of the dorsolateral prefrontal cortex, the anterior insula, the dorsal anterior cingulate, the pre-supplementary motor area, and the intraparietal sulcus. Previous studies have demonstrated that these gradients can be influenced by various factors, including disorders such as depression (19) and autistic spectrum disorder (20), as well as cognitive and psycho-affective training (21). Interestingly, psychedelics, such as psilocybin (22) and N,N-Dimethyltryptamine (DMT) (23) can induce ego dissolution and are correlated to a collapse of the cognitive hierarchy as measured by the first gradient.…”
Section: Introductionmentioning
confidence: 99%
“…This network is composed of the inferior frontal sulcus, regions of the dorsolateral prefrontal cortex, the anterior insula, the dorsal anterior cingulate, the pre-supplementary motor area, and the intraparietal sulcus. Previous studies have demonstrated that these gradients can be influenced by various factors, including disorders such as depression (19) and autistic spectrum disorder (20), as well as cognitive and psycho-affective training (21). Interestingly, psychedelics, such as psilocybin (22) and N,N-Dimethyltryptamine (DMT) (23) can induce ego dissolution and are correlated to a collapse of the cognitive hierarchy as measured by the first gradient.…”
Section: Introductionmentioning
confidence: 99%